2021
DOI: 10.1007/s10539-021-09790-6
|View full text |Cite
|
Sign up to set email alerts
|

Out of our skull, in our skin: the Microbiota-Gut-Brain axis and the Extended Cognition Thesis

Abstract: According to a shared functionalist view in philosophy of mind, a cognitive system, and cognitive function thereof, is based on the components of the organism it is realized by which, indeed, play a causal role in regulating our cognitive processes. This led philosophers to suggest also that, thus, cognition could be seen as an extended process, whose vehicle can extend not only outside the brain but also beyond bodily boundaries, on different kinds of devices. This is what we call the ‘Externally Extended Cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 140 publications
0
13
0
Order By: Relevance
“…Gut microbiome–brain interactions, both as a construct (Boem et al., 2021; Martin et al., 2018; Sarkar et al., 2018) and as a constellation of phenomena (Cusick et al., 2021; Cussotto et al., 2018; Nagpal & Cryan, 2021), have stimulated vigorous activity in basic, translational, and clinical research. Among the many remarkable findings are data suggesting links between early life ABx exposure, GI issues—including dysbiosis—and ASDs (e.g., Adams et al., 2007; Atladóttir et al., 2012; Axelsson et al., 2019b; Bittker & Bell, 2018; Guisso et al., 2018; Hisle‐Gorman et al., 2018; Vargason et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiome–brain interactions, both as a construct (Boem et al., 2021; Martin et al., 2018; Sarkar et al., 2018) and as a constellation of phenomena (Cusick et al., 2021; Cussotto et al., 2018; Nagpal & Cryan, 2021), have stimulated vigorous activity in basic, translational, and clinical research. Among the many remarkable findings are data suggesting links between early life ABx exposure, GI issues—including dysbiosis—and ASDs (e.g., Adams et al., 2007; Atladóttir et al., 2012; Axelsson et al., 2019b; Bittker & Bell, 2018; Guisso et al., 2018; Hisle‐Gorman et al., 2018; Vargason et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…First, bacteria also seem to employ quorum sensing to communicate with plants and animals (Lowery et al, 2008). This idea might have potential implications for other philosophical claims, such as the suggestion that microbiota 'extend our minds' (Boem et al 2021). Secondly, it has been suggested that bacteria like B. subtillis communicate using electrical signals, which might have close analogies with neuronal communication by means of action potentials (Prindle et al 2015;Beagle and Lockless, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Should a holobiont be considered a physiological organism? Three arguments, namely (i) activity, (ii) spatiotemporal position, and (iii) tolerance of the immune system, support the physiological concept of the holobiont as a genuine organism (Bordenstein and Theis, 2015;Stencel and Proszewska, 2018;Triviño and Suárez, 2020;Boem et al, 2021).…”
Section: The Physiological View Of Organisms and Holobiontsmentioning
confidence: 90%